The Role of Families in Preventing Coronavirus Disease : Review Literature - Nurfitria, Atika (Jurnal Kesehatan Madani Medika, 2023)
Background: The role of the family occupies an important and strategic position in preventing the covid-19 disease outbreak. These roles include recognizing family members' health problems, making appropriate health action decisions, providing care to families experiencing health problems, modifying the environment to support the healing process and using available public health facilities. The role of the family is very important during the COVID-19 pandemic to form a healthy lifestyle in accordance with applicable health protocols. Purpose: The purpose of this literature review is to find out the role of the family in preventing Covid19. Research Methodology: Research using Literature Review. Research article search strategy uses google scholar, researchgate and science direct databases. Articles published in 2019-2021 and the keywords used, the role of the family, the corona virus disease. Results: Based on the results of the 10 articles reviewed, it was found that the role of the family has an important role in preventing Covid-19. The role of the family is to recognize family health problems, decide on appropriate health measures for the family, care for families with health problems, modify the family environment to support the healing process to prevent the spread of Covid-19 and take advantage of available health care facilities. Conclusion: The role of the family is very important in preventing covid-19, the role of the family is needed in terms of forming a healthy lifestyle, the family as a center of nursing (family-centered nursing) is based on the perspective that the family is the basic unit for individual care of family members. Keywords: Role of Family, Prevention, Covid-19.